THE INFLUENCE OF LEADERSHIP AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT DINAS PARIWISATA KOTA BITUNG - Biera, Ardwin; Tumbuan, Willem J. F. A.; Tielung, Maria V. J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
This study aims to analyze the influence of leadership and organizational culture on employee performance at Dinas Pariwisata kota Bitung. The data used in this study are primary data of 74 respondents with a questionnaire or questionnaire method. The method used to analyze the relationship between the independent variable and the dependent variable is a multiple linear regression method and classical assumption test. The results of this study indicate that simultaneously, leadership and organizational culture have an effect on employee performance. This means that these two variables can have an influence on the performance of the employees of Dinas Pariwisata kota Bitung simultaneously, partly. Leadership has a positive and significant effect on employee performance at the Dinas Pariwisata kota Bitung. Likewise, organizational culture has a positive and significant effect on the performance of the Dinas Pariwisata kota Bitung employees.Â Keywords: leadership, organizational culture, employee performance